Waiting 'til the last minute motivations and outcomes of academic procrastination of U.P. College of Home Economics students - Samson, Jennifer T.; Samson, Jillian Tuazon; Tongson, Excelsa C. (Quezon City College of Home Economics, University of the Philippines Diliman, 2010)
ABSTRACT The study aims to determine the motivations and outcomes of academic procrastination on U.P. College of Home Economics (CHE) undergraduate students. Other objectives are to determine the type of subject and academic task that CHE students most procrastinate on, the characteristics of a teacher, subject, and academic task that influence procrastination, and the reasons to maintain or eliminate their academic procrastination. Responses from 100 CHE students were gathered through survey and focus group discussions conducted to the classes of HE 100 and HE 101, two required subjects for CHE students thus all seven undergraduate programs of the college are represented. Quota sampling for the survey and convenience sampling for focus group discussions were used. Frequencies, percentages, modes, and thematic tables were used to analyze data. Results show CHE students procrastinate more on GE subjects and reading assignments and exams. Motivations for academic procrastination include time reference, ?recency effect?, laziness, too many things to do, leisure, underestimation of time and difficulty of task, better performance, insufficient energy, family, and peers. Teacher characteristics include if the teacher calls for recitation, leniency, strictness, and kindness, and liveliness. Subject characteristics include difficulty, prerequisite nature, and interest in subject. Academic task characteristics include task appeal, difficulty, and length. Stress and anxiety, lack of sleep, absences in classes, unfinished or mediocre works, poor grades, cheating and plagiarism, decline in health, negative feelings, and negative influences to others were the identified negative outcomes of academic procrastination. Satisfactory outputs, better performance, skills development, time for family, friends, leisure, rest, less time spent doing a task, sense of accomplishment and self-handicapping were the identified positive outcomes. Lastly, CHE students want to eliminate their procrastination to increase productivity, eliminate stress, avoid influencing others negatively, and attain professional success.
Thesis (B.S. Family Life and Child Development)--University of the Philippines Diliman.
Keywords: College students -- Philippines; Procrastination